Non-monetary benefit sharing mechanisms within the projects funded by the Benefit Sharing Fund: Second meeting of the Ad Hoc Open-ended Working Group to Enhance the Functioning of the Multilateral System of Access and Benefit-sharing. Geneva (Switzerland) 9-11 Dec 2014 - Galluzzi, G.; López Noriega, Isabel; Halewood, Michael; Bioversity International (Food and Agriculture Organization of the United Nations, 2014)
This study presents and overview of the projects that have been funded by or proposed to the Benefit-sharing Fund (BSF) under the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPRFA). In particular, the study focusses on the technology transfer, capacity building and information exchange-related activities that are included in those projects.